Implementasi Artificial Intelligence Pada Praktik Manajemen Di Kantor Dinas Pendidikan & Kebudayaan Kota Malang - Zainurrokhim, Zainurrokhim; Pardiman, Pardiman; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the implementation of artificial intelligence (AI) in management practices at the Malang City Education and Culture Office. The background of this research is based on the challenges of digital transformation in the public sector, particularly at the local government level, which has not fully utilized the potential of AI. This study uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and document analysis. The informants in the study consisted of structural officials and technical staff relevant to the management of the information system within the agency. The research findings indicate that understanding of AI technology is still limited and has not yet become part of the agency's strategic policy. Human resources show high enthusiasm, especially from the younger generation, but still require technical training and ongoing mentoring. The lack of specific policy guidance from leadership is a constraint in planning and budgeting for AI-based programs. Relevant and realistic forms of AI implementation include internal service chatbot systems, automated employee data management, and analysis of educational infrastructure needs. This research recommends the importance of phased planning, strengthening human resource capacity, and more progressive policy support to promote the sustainable adoption of AI in the local public sector. Keywords: Artificial Intelligence, Public Management, Digital Transformation, Local Government, Education Department.